MARKETING TOOLS TO ENSURE THE ECONOMIC SECURITY OF THE ENTERPRISE: THE ESSENCE AND CLASSIFICATION - ASAMOAH KYEREMEH, JOSHUA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the article a role and value of marketing and his instruments are certain with the aim of providing of economic security of enterprise. On results what reached to the conclusion, that marketing activity of enterprise is one of functional constituents of economic security of enterprise, that can positively on her influence through implementation in practical activity of corresponding marketing instruments. The structural elements of economic security of enterprise are analysed. The semantic filling of marketing constituent of economic security of enterprise that envisages the presence of next elements is outlined, in particular: subjects, aim of realization of marketing constituent of economic security of enterprise, mechanism of realization and objects. Authorial determination over of category is brought "marketing instruments" that will be used with the aim of providing of economic security of enterprise. The necessity of realization of classification of marketing instruments and classification signs are offered and systematized corresponding marketing instruments in accordance with each of them. The brought classification over allows complex to overcome of marketing activity of enterprise and her influence on economic security. The basic tasks of instruments to marketing are certain in the context of providing of economic security of enterprise. Attention is accented on changes, that took place in the field of marketing as a result of the transformation of marketing environment, caused by distribution of Covid, - 19. In particular, it is marked that by the most popular and effective instruments of marketing, that are used in the modern terms of menage there are internet-marketing instruments that provide for forming the newest on-line marketing environments.